Proposição de um framework para o desenvolvimento de aplicações móveis sensíveis ao contexto - Magalhães, Clayton (2020)
Current mobile devices have the ability to collect context information from the user in a non-intrusive and integrated way, through internal and external sensors. This technological advance opens up many possibilities for the development of applications, especially those sensitive to the context. As they present many challenges and specificities in relation to traditional systems, some initiatives have been proposed for the process of developing this type of application. These initiatives are concentrated in different stages of the project, as well as proposing different models of context representation. However, none of them addresses functional and architectural requirements, providing practical tools and instructions for implementation. This work aims to propose a framework for the development of context-sensitive mobile applications, through representation models, architecture and integrated implementation guidelines, considering principles of modularity, scalability and compatibility. In addition, it gathers and adapts different models from the literature, applying the same concepts in a complementary way. It also addresses current issues such as storage and power limitations on mobile devices, as well as connection availability. To verify the assertiveness of the conceptual model and the proposed architecture, an assessment was made with three systems analysts who were able to read and practice the proposed concepts, answering a feedback questionnaire, generally positive and with suggestions. A mobile application with context-sensitive features was also developed, focused on food care and tested by six nutrition professionals. After a period of use of seven days, the professionals answered a perception questionnaire regarding the features with context sensitivity. The data was analyzed and, in general, users also gave positive feedback. As a conclusion, the application built from the framework verified the viability of the proposed structure through its practical use primarily with software professionals and in an example domain. It is expected, with this work, to contribute to the computing area, with the availability of a framework for context sensitive applications.